THE EFFECT OF FIRM SIZE, LEVERAGE, INDEPENDENT AUDIT COMMITTEE, INSTITUTIONAL OWNERSHIP ON CORPORATE RISK DISCLOSURE - Christine Surya (Fakultas Ekonomi Universitas Advent Indonesia, 2018)
Corporate risk disclosure as a disclosure of the present or future situation that is not desired by the company and has the potential to occur and includes handling the risks carried out by the company. Disclosure is required for a transparency firm. This study was aimed to find out the effect of firm size, leverage, independent audit committee, institutional ownership on corporate risk disclosure. Statistical analysis method used in this research was multiple regression analysis method. The results of this study found out that larger company size and larger institutional ownership will increase corporate risk disclosure while leverage and independent audit committee reduce corporate risk disclosure. The other results implied from this study that firm size, leverage, independent audit committee and institutional ownership simultaneously influence and increase corporate risk disclosure. Optimal disclosure is needed so that information reaching various parties is a reflection of actual events and the quality of decisions taken would be better